2006
DOI: 10.1002/dvdy.21020
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral junctions are sufficient to suppress epithelial invasion during Drosophila oogenesis

Abstract: Epithelial junctions play crucial roles during metazoan evolution and development by facilitating tissue formation, maintenance, and function. Little is known about the role of distinct types of junctions in controlling epithelial transformations leading to invasion of neighboring tissues. Discovering the key junction complexes that control these processes and how they function may also provide mechanistic insight into carcinoma cell invasion. Here, using the Drosophila ovary as a model, we show that four prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 53 publications
0
64
2
Order By: Relevance
“…32 Most recently, we showed that scrib genetically interacts with dlg in posterior patterning of ovarian follicular epithelium. 37 Considering that lgl, dlg and scrib work in concert to regulate cell polarity and proliferation in the epithelial tissues, 10,18,19,22,23,[38][39][40][41][42] we intended to determine whether these three genes act in a common pathway to function in PFC specification and differentiation. To address this issue, we tested for genetic interactions among the three mutations and detected strong interactions of lgl with dlg and scrib in the examined process.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Most recently, we showed that scrib genetically interacts with dlg in posterior patterning of ovarian follicular epithelium. 37 Considering that lgl, dlg and scrib work in concert to regulate cell polarity and proliferation in the epithelial tissues, 10,18,19,22,23,[38][39][40][41][42] we intended to determine whether these three genes act in a common pathway to function in PFC specification and differentiation. To address this issue, we tested for genetic interactions among the three mutations and detected strong interactions of lgl with dlg and scrib in the examined process.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…10,18,19,[22][23][24][25][26] We and others have shown that lgl/dlg/scrib are required for a number of developmental controls during oogenesis. 10,[18][19][20]22,23,[27][28][29][30][31][32][33][34][35][36] In particular, we have identified Lgl as an essential regulator in PFC specification and differentiation, and a role of dlg/scrib in both anterior and posterior patterning of the follicular epithelium. 32,37 In this paper, we show that lgl genetically interacts with dlg/scrib in PFC fate induction, suggesting a common regulatory pathway in this process.…”
Section: Introductionmentioning
confidence: 99%
“…A universal theme is that each type of epithelial junction is organized by a transmembrane receptor bound to a cytoplasmic scaffolding protein, thus enabling assembly of a supermolecular complex of proteins within the cellular cortex at sites of intercellular contact (Knust 2002). Epithelial junctions are relatively stable in stationary epithelia, but they undergo extensive remodeling when epithelia transform into migratory cells during embryonic development, tissue repair and regeneration, and pathological conditions such as cancer (Grunert et al 2003;Shook and Keller 2003;Szafranski and Goode 2004;Larue and Bellacosa 2005;Thiery and Sleeman 2006;Szafranski and Goode 2007). Understanding how epithelial junctions are used for epithelial maintenance and epithelial remodeling during normal development may allow targeting tumor invasion without perturbing normal tissue homeostasis.…”
mentioning
confidence: 99%
“…Once follicle cell proliferation ceases, differentiation begins, setting the stage for two migration events during midoogenesis. A small cluster of cells that reside in the anterior epithelium, called border cells (BC), undergo a partial epithelial-mesenchymal transition (EMT), break free from adjacent epithelial cells, and migrate posterior between the nurse cells to the oocyte (Figure 2A) (Niewiatomska et al 1999;Starz-Gaiano and Montell 2004;Szafranski and Goode 2007). At the same time, most follicle cells that surround the nurse cells move posterior to encapsulate the oocyte (Goode et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation